Efficacy and safety of tranexamic acid in reducing hidden blood loss during unilateral total knee arthroplasty: a retrospective study - Liangliang, Luo; Wei, Huang; Tao, Zhang; Pin, Pan; Lianying, Hu (Frontiers in Medicine, 2025)
This retrospective study evaluates the efficacy and safety of tranexamic acid (TXA) in reducing hidden blood loss during unilateral total knee arthroplasty (TKA) in patients with osteoarthritis. As the aging population leads to a rise in degenerative knee joint diseases, TKA has become a common surgical intervention. However, it is often associated with significant hidden blood loss, accounting for 60–75% of total blood loss, which can result in complications such as anemia and increased transfusion needs. Our study included 123 patients who underwent TKA between June 2019 and June 2022, divided into an observation group receiving TXA and a control group receiving saline. TXA was administered intravenously before surgery and locally into the joint cavity post-incision. The study found that TXA significantly reduced total blood loss by 37.4%, with a notable decrease in hidden blood loss (p < 0.05). The TXA group also exhibited lower transfusion rates (27.4 vs. 45.9%, p = 0.033) and reduced intraoperative blood loss (330.6 ± 25.3 mL vs. 494.4 ± 32.8 mL, p < 0.001). Importantly, TXA did not increase the risk of thromboembolic complications, with no significant differences in deep vein thrombosis or pulmonary embolism between the groups. Coagulation parameters remained stable, supporting TXA’s safety profile. These findings suggest that TXA is a safe and effective strategy for managing blood loss in TKA, potentially improving patient outcomes, reducing healthcare costs, and optimizing resource utilization.